Assessment of Antioxidative and Alpha-Amylase Potential of Polyherbal Extract. (31st May 2022) - Patwekar, Mohsina; Patwekar, Faheem; Mezni, Amine; Sanaullah, Syed; Fatema, Shaikh Rohin; Almas, Ustad; Ahmad, Irfan; Tirth, Vineet; Mallick, Jewel
Abstract : The present study aims to prepare a polyherbal formulation (PHF) of Azadirachta indica (Neem), Aloe barbadensis (Aloe vera), Allium sativum (garlic), Acacia arabica (Babul), and Aegle marmelos (Bel) and evaluation of antidiabetic and antioxidant activity utilizing the in vitro model. Air-dried powder of 5 medicinal plants, which are divided into equal portions, and PHF, is prepared by the soxhlet technique using polar and nonpolar solvents. The PHF is screened for the phytochemical screening, and then the antidiabetic activity is determined by alpha-amylase inhibition. The extracts thus obtained are also subjected to the inhibition assay by the use of (DNS) dinitro salicylic acid. The antioxidant activity was determined by the DPPH radical scavenging assay, H2 O2 scavenging assay, and TBARS assay. In in vitro study, the result revealed polyherbal formulation in which hot water extract has the topmost inhibitory effect on alpha-amylase activity, ranging from 20.4% to 79.5% with an IC50 value of 48.98 ± 0.31  μ g/ml. This extract clearly showed the effective lowering of postprandial hypertriglyceridemia (PPHG). In the antioxidant activity carried out by using the (DPPH) radical scavenging assay, the highest result was obtained by the concentration of 250  μ g/ml, which was around 77.2 ± 0.05 with statistical significance compared with control (a: p < 0.01 ; b: p < 0.001 ), while in the GTA method, the highest result was obtained by the concentration of 250  μ g/ml, which was around 78.2 ± 0.05, and in the case of the TBARS assay, the concentration of 250  μ g/ml gave around 76.2 ± 0.03 anti-oxidant value. In conclusion, the study shows that polyherbal formulation has superior antidiabetic activity and antioxidant properties.